2008
DOI: 10.1007/s11139-007-9108-7
|View full text |Cite
|
Sign up to set email alerts
|

Global asymptotics for Laguerre polynomials with large negative parameter—a Riemann-Hilbert approach

Abstract: In this paper, we study the asymptotic behavior of the Laguerre polynomials L (α n ) n (nz) as n → ∞. Here α n is a sequence of negative numbers and −α n /n tends to a limit A > 1 as n → ∞. An asymptotic expansion is obtained, which is uniformly valid in the upper half plane C + = {z : Im z ≥ 0}. A corresponding expansion is also given for the lower half plane C − = {z : Im z ≤ 0}. The two expansions hold, in particular, in regions containing the curve in the complex plane, on which these polynomials are ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…After transforming the discrete RHP associated with this polynomial into a specific continuous one, we find that this problem is similar to some of the problems considered previously (see, e.g., [23], [24] and [26]), and our method in [5] can be applied. More precisely, for 0 < c < p, we present an infinite asymptotic expansion which is valid uniformly in the whole complex plane bounded away from (−∞, 0] and [1, ∞).…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…After transforming the discrete RHP associated with this polynomial into a specific continuous one, we find that this problem is similar to some of the problems considered previously (see, e.g., [23], [24] and [26]), and our method in [5] can be applied. More precisely, for 0 < c < p, we present an infinite asymptotic expansion which is valid uniformly in the whole complex plane bounded away from (−∞, 0] and [1, ∞).…”
Section: Introductionmentioning
confidence: 56%
“…Furthermore, by successive approximation (see [5]), it can be easily demonstrated that the expansion (3.59) holds uniformly for all…”
Section: The Expansion In (357) Is Uniformly Valid For All X ∈ [1 ∞)mentioning
confidence: 98%
See 3 more Smart Citations